Sifat Fisik, Kimia dan FTIR Spektrofotometri Gambut Hidrofobik Kalimantan Tengah - Sri Nuryani Hidayah Utami; Azwar Maas; Bostang Radjagukguk; Benito Heru Purwanto (JOURNAL OF TROPICAL SOILS, 2009)
Nature on Soil Phisical, Chemical and Ftir Spectrophotometry of Hydrophobic Peat From Central Kalimantan (S.N.H. Utami, A. Maas, B. Radjagukguk, and B.H. Purwanto): Peat soils naturally have hydrophilic or water-loving character with highly capable of exchanging the cations and cycling the nutrients from the vegetations. This water-loving character is altered to water-repellent character in hydrophobic peat soils. This research was aimed to observe deeply the functional bunch carrier of hydrophobic and hydrophilic peat soils as shown by FTIR spectra in relation with inherent chemical and physical properties of the soils. Five peat soils consisted of two native and artificial hydrophobic peat soils and one sample of hydrophilic peat soils were studied. Artificial hydrophobic peat soils were yielded by oven-drying the native hydrophobic peat soils at 50 oC for 10 hours. FTIR spectra can distinguish the functional bunch carrier of hydrophobic and hydrophilic peat soils. FTIR spectra of hydrophobic peat soils showed degradation of hydrophilic bunch carrier (¾OH and ¾COOH) and increase of the hydrophobic bunch carrier (tying aromatic from esther and ether). Chemical analysis  of the hydrophobic peat soils also indicated the decrease of ¾OH and ¾COOH content, decrease of CEC , soil total acidity and soil moisture content.